Future Trends in Healthcare Technology - Li, C. K; Fong, Bernard; Fong, A. C. M (Telemedicine Technologies, 2020)
This chapter examines areas where telemedicine technology will gain more interest. It looks at proven digital health technologies in tackling real life challenges, and discovers how emerging technologies can be reliably deployed in a number of selected scenarios in the foreseeable future in the telemedicine context, based on currently available technologies. Haptic sensing reacts to the user's hand movement including forces, vibrations, and motions. Control based on haptic sensing would be limited by friction, precision, and lack of stimulus for the sense of touch. Cyber physical systems are monitored and controlled by computer‐based algorithms thereby reduces the need of electronic hardware while enhancing the utilization efficiency of resources. Syndromic surveillance can be used for both natural as well as manmade intentional bio‐attack. Advances in wearable sensors make 5G an important infrastructure for remote health monitoring that can be used in different entities within a smart city like homes, buildings, and on the roads.